Association between agronomic traits and metabolite profiles on yield response and water use efficiency in newly developed wheat populations under drought stressed conditions - Maltase Mutanda; Hussein Shimelis; Vincent Chaplot; Ntakadzeni E. Madala; Sandiswa Figlan (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
Multiple trait selection guides the deployment of wheat varieties with high grain yield (GY) and water-use efficiency (WUE). The study aimed to determine the degree and trend of association between agronomic traits and major metabolites to identify influential traits and metabolites optimised by wheat genotypes for improved GY, WUE and drought tolerance. One hundred wheat genotypes were evaluated under drought-stressed (DS) and non-stressed (NS) using a 5 × 20 alpha-lattice design with two replications. The recorded agronomic traits included GY, shoot biomass (SB), root biomass (RB) and plant biomass (PB). The WUE in relation to GY (WUEgy) was computed based on GY produced under DS and NS. The grain of 10 wheat genotypes with high GY under DS were assayed for their metabolic responses to DS. The WUEgy showed significant correlations with PB, RB and SB under DS and NS conditions. Citric acid was strongly correlated with GY and WUEgy than other metabolites under DS. The SB had high positive direct effects on GY under both treatments, while PB had high and positive direct effects on WUEgy under DS. Therefore, selection based on SB, PB and citric acid is effective when selecting wheat ideotypes for drought tolerance and WUE.